Cybersecurity awareness among youth in Brunei Darussalam - Mohammad Bakhtiar Haji Roslan (Kulliyyah of Information Communication Technology, International Islamic University Malaysia, 2022)
Cybersecurity is vital in the modern era as more and more people, especially youth are using gadgets and the internet for many purposes such as working, learning, business, and entertainment, particularly during and post Covid-19 pandemic. Due to the cybersecurity cases involving youth, it shows that some youth does not know how to utilize cybersecurity to protect them from becoming victim of cybercriminals but also facing other cyber safety and security issues and challenges that are not considered as crimes. There are a lot of cases where children and youth become victims of cybercrimes due to their lack of awareness or knowledge about cybersecurity. For example, using similar passwords for all their social media accounts or using public Wi-Fi that is not password protected. This research aims determine the level of cybersecurity awareness among youth and proposes a module for cybersecurity awareness programs in Brunei Darussalam. This research used qualitative method and semi structured interview to obtain data. For the recruitment of participants, convenience and purposive sampling are used together. The outcome of the findings has led to the creation of four central themes: 1) Knowledge on cybersecurity 2) Behavior in cybersecurity 3) Security measures in protecting devices, information, and online activities and 4) Preferred method in delivering security knowledge and awareness. Based on our findings, the youth in Brunei Darussalam are actually aware of cybersecurity even though most do not have IT background. However, the youth still need to be reminded and update their cybersecurity knowledge. This is because technology evolves now and then, the same goes for threats. Therefore, it is recommended that Brunei government agencies, NGOs and private institutions must find a suitable and effective methods of delivering cybersecurity knowledge.